CHEST X-RAY: AN UNFAIR SCREENING TOOL - Naz, Saima; Aziz, Tahir; Umair, Malik Mohammad; Uzair, Malik Mohammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Chest radiography is considered as the sole screening tool for chest pathologies as prerequisite for overseas employment during their medical examinations. The aim was to evaluate the role of CXR as a screening tool in the diagnosis of different lung pathologies in general and TB in particular. Methods: In this descriptive case series, reports of 63,648 Pakistani candidates, who took chest X-rays during medical screening for employment abroad under the rules of Gulf Coordination Council (GCC), were analysed. The reports were collected over a three year period (2008-2011). All the candidates were apparently healthy males of ages ranging between 18-50 years with average age of 27.4 years. Results: Out of 63,648 candidates examined over a three year period, 1368 (2.15%) were declared unfit on the basis of CXR. There were 359 cases of calcified granulomas, 318 of costophrenic angle obliteration, 174 of apical scaring; 144 of pulmonary scars, 123 of fibrocalcific lesion, 82 of soft shadows in lung, 51 of nodular lung shadows, 42 of lymphadenopathy, 30 of pleural effusion, 26 of interstitial lung shadow and 19 of calcification. A closer scrutiny of these cases revealed that over 90% of the CXRs of the candidates declared as having lung pathologies displayed scars rather than active disease. Conclusion: A normal CXR by itself, neither categorically rules out problems in the chest nor does any finding in it confirm some disease. Unfitness on the basis of CXR alone, unless substantiated by further investigation, is questionable to say the least. Keywords: Chest radiography, pre-employment, screening, misdiagnosis, Tuberculosis